Dalitz plot analyses of B0 → D-D0K+ and B+ → D0D0K+ decays - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We present Dalitz plot analyses for the decays of B mesons to D−D0K+ and ¯D0D0K+. We report the observation of the D∗s1(2700)+ resonance in these two channels and obtain measurements of the mass M(D∗s1(2700)+)=2699+14−7 MeV/c2 and of the width Γ(D∗s1(2700)+)=127+24−19 MeV, including statistical and systematic uncertainties. In addition, we observe an enhancement in the D0K+ invariant mass around 2350-2500 MeV/c2 in both decays B0→D−D0K+ and B+→¯D0D0K+, which we are not able to interpret. The results are based on 429 fb−1 of data containing 471×106B¯B pairs collected at the Υ(4S) resonance with the BABAR detector at the SLAC National Accelerator Laboratory.